Data-Based Planning Transformation in Monitoring and Evaluation of School Programs: Towards Improving the Quality of Education - Amiruddin, Amiruddin; Chardo, Chardo (Indonesian Journal Education, 2023)
Compared with other countries, education in Indonesia is still relatively low. This is caused by the lack of use of data in planning, monitoring and evaluating school programs. Planning without data is often ineffective and does not achieve the expected goals. This research aims to analyze the transformation of data-based planning in monitoring and evaluating school programs to improve the quality of education. This research uses a qualitative descriptive method with a literature study approach. Data was collected through reviewing literature, such as scientific journals, scientific articles and relevant books. The research results show that the transformation of data-based planning in monitoring and evaluating school programs can improve the quality of education. This can be achieved by: 1) Utilizing data to assist in decision making. 2) Measure program progress periodically. 3) Identify areas that need improvement. 4) Increase school accountability. 5) Improve student learning outcomes. This research makes a significant contribution to the field of education, especially in terms of planning, monitoring and evaluating school programs. The results of this research can be used by schools to improve the quality of education through effective use of data